Contribution of Female Farm Workers in Improving the Standard of Living of Families in Montong Goak Hamlet Sisik Village Pringgarata District - Rizkah; Ningsih, Dewi Puspita; Apriawan, Andika; Di Biagi, I Wayan Kusuma (International Journal of Social Sciences and Humanities, 2023)
This study aims to determine and analyze the contribution of female farm laborers in improving the standard of living of families and the factors of women working as farm laborers. This study uses a qualitative research type with a descriptive approach. By determining informants using purposive techniques with the criteria of housewives who work as farm laborers in Montong Goak Hamlet, Sisik Village, Pringgarata District, Central Lombok Regency. Data collection techniques are carried out through observation, interviews and documentation. The results of this study indicate that female farm laborers who work for other people solely to get wages/salaries in the form of money or goods, women who have dual roles, namely as wives, mothers and working as laborers, women participate in contributing to improving the family economy to be able to help ease the burden on their husbands and can meet the needs of family members with the results of working as farm laborers. Women have a big influence in improving the family's standard of living, namely the results of working as laborers can meet daily needs, basic needs, children's education needs, health and help in contributing to social needs and can carry out dual roles well. Female farm laborers are very helpful in improving the family's standard of living so that in this study, informants were generally in the living conditions of KS I, KS III and KS III.